2003
DOI: 10.2337/diacare.26.9.2616
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Vasomotor Response of the Radial Artery in Patients With Diabetic Foot Syndrome

Abstract: ANJA VICTOR, BS 5OBJECTIVE -Neurophysiological assessment of the peripheral autonomic system is characterized by various limitations. An alternative approach to laser Doppler and venous plethymography is the assessment of the sympathetic vasomotor response of the radial artery obtained by continuous wave Doppler sonography. Nomogram data have been established and demonstrate the temporary disappearance of diastolic flow after coughing or deep inspiration. RESEARCH DESIGN AND METHODS -We assessed the sympatheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…In this study, PI increased, while Vmax, Vmin, and TAMaxV decreased in both the young and the older groups after coughing (Table 1 and 2). This finding is consistent with previous studies showing that sympathetic arterial vasoconstriction can be elicited in adults at any age 1, 3, 15. At rest, the vasomotor tone reflected by PI showed no significant difference between the two groups (Tables 1 and 2 and Figure 5).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, PI increased, while Vmax, Vmin, and TAMaxV decreased in both the young and the older groups after coughing (Table 1 and 2). This finding is consistent with previous studies showing that sympathetic arterial vasoconstriction can be elicited in adults at any age 1, 3, 15. At rest, the vasomotor tone reflected by PI showed no significant difference between the two groups (Tables 1 and 2 and Figure 5).…”
Section: Discussionsupporting
confidence: 92%
“…The latency of SSR is known to increase significantly with age 14. Although SSR was previously considered to be age‐independent,1, 3, 15 few studies compared the magnitude of this response between young and older people. We therefore designed a study to evaluate the effect of aging on the sympathetic vasomotor response as shown by a change in vascular resistance indirectly reflected in the pulsatility index 16…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous comparison of laser Doppler flowmetry of the fingertips and flow changes in the radial arteries in patients with autonomic disorders has yet not been reported. However, our previous data, obtained from patients with a diabetic foot syndrome [5], were in accordance with LDF studies [9]. Both studies showed a decreased sympathetic vasoconstriction due to external stimuli, electrically induced or by cough.…”
Section: Discussionsupporting
confidence: 70%
“…Nomogram data have been established from our group and demonstrate the temporary disappearance of diastolic flow after coughing or deep inspiration [4,15]. Compared with healthy volunteers, the flow pattern in patients with a diabetic foot syndrome shows a different profile with a bior triphasic flow at baseline indicating a reduced distensibility of the vessel walls and a delayed onset of reaction as evidence of neuropathic damage of the sympathetic fibres [5]. As the flow profile of the radial artery is obtained in a vessel segment proximal to the vascular resistance vessels (i. e. arterioles), these data need to be correlated with LDF, the standard measurement of microcirculatory blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using continuous wave Doppler ultrasound to assess SVR in patients with diabetic neuropathy or carpal tunnel syndrome indicated that reduced elevations in pulsatility or resistive index after stimulation implied impairment in the corresponding sympathetic circuits [15, 16]. However, for patients with MSA, the deficit in sympathetic neurotransmission was known to be preganglionic, therefore the indicators for peripheral vasoconstriction like pulsatility index may remain normal as controls [3].…”
Section: Discussionmentioning
confidence: 99%